2020
DOI: 10.3390/cancers12123543
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Intentions to Engage in Risk-Reducing Behaviours after Receiving Personal Ovarian Cancer Risk Information: An Experimental Survey Study

Abstract: Risk stratification using genetic and/or other types of information could identify women at increased ovarian cancer risk. The aim of this study was to examine women’s potential reactions to ovarian cancer risk stratification. A total of 1017 women aged 45–75 years took part in an online experimental survey. Women were randomly assigned to one of three experimental conditions describing hypothetical personal results from ovarian cancer risk stratification, and asked to imagine they had received one of three re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…RRSO is cost‐effective at 4–5% or more lifetime ovarian cancer risk thresholds 73,88 . This saves seven to ten years of a woman's life and has been found to be acceptable 73,88,89 . This 4–5% lifetime ovarian cancer risk threshold has been supported by a Royal College of Obstetricians and Gynaecologists scientific impact paper 56 and a UK Cancer Genetics Group consensus statement 55 .…”
Section: Surgical Prevention For Women At Increased Risk Of Ovarian C...mentioning
confidence: 97%
See 1 more Smart Citation
“…RRSO is cost‐effective at 4–5% or more lifetime ovarian cancer risk thresholds 73,88 . This saves seven to ten years of a woman's life and has been found to be acceptable 73,88,89 . This 4–5% lifetime ovarian cancer risk threshold has been supported by a Royal College of Obstetricians and Gynaecologists scientific impact paper 56 and a UK Cancer Genetics Group consensus statement 55 .…”
Section: Surgical Prevention For Women At Increased Risk Of Ovarian C...mentioning
confidence: 97%
“…73,88 This saves seven to ten years of a woman's life and has been found to be acceptable. 73,88,89 This 4-5% lifetime ovarian cancer risk threshold has been supported by a Royal College of Obstetricians and Gynaecologists scientific impact paper 56 and a UK Cancer Genetics Group consensus statement. 55 An American group suggested a lower 3-4% lifetime ovarian cancer risk threshold be considered.…”
Section: Risk-reducing Salpingo-oophorectomymentioning
confidence: 98%
“…A pilot study of a general population women who self-referred themselves for the study based on leaflets made available at primary care practices, demonstrated feasibility, acceptability, high uptake, and satisfaction with risk assessment approaches along with a reduction in cancer risk perception and worry with time [ 23 ]. General population surveys have shown that women are keen to know their personalized cancer risk and would undergo surgical prevention if found to be at increased risk [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This sets the stage for larger implementation studies to follow. In a randomised experimental survey of general population women, Gallagher et al [ 3 ] show that women are willing to undergo risk reducing surgery to reduce their ovarian cancer risk at a range of risk levels and that uptake rates are similar for 5–10% and >10% life time ovarian cancer risks. For the first time, Manchanda et al [ 4 ] demonstrate the cost-effectiveness of population-based BRCA testing across multiple high income and upper middle income countries health systems (USA, UK, Netherlands, China and Brazil).…”
mentioning
confidence: 99%